Youth-Oriented Public Space Regeneration in Historic Districts: A Participatory IPA-Based Evaluation in Beijing’s Fayuan Temple Area - Qin Li; Wenao Liu; Runhao Zhang; Yijun Liu; Lixin Jia (Buildings, 2026)
In recent years, the agentive role of youth groups in urban regeneration has garnered increasing academic attention. As vital carriers of urban cultural heritage, the ways in which historic districts can leverage youth dynamics to achieve vitality revitalization have emerged as a key research issue. This study selects the Fayuan Temple Historic and Cultural District in Beijing as an empirical case, constructs a public space evaluation system grounded in the concept of “youth-friendliness,” adopts a mixed-method approach integrating field surveys, questionnaire administration, and multi-source data mining, and employs Importance–Performance Analysis (IPA) modeling for deconstruction. Based on behavioral characteristic differences, youth within the district are categorized into two groups: “resident/local youth” and “transient visiting youth.” The comprehensive experience quality scores were 3.559 (Fair) for resident and local youth and 3.85 (Fair) for temporary visitors, with cultural space scoring highest for both groups. Resident youth demonstrate stronger demands for renewal concerning the completeness of cultural facilities, diversity of commercial formats, and street navigability. Transient visiting youth, by contrast, exhibit greater concern for eight factors: pedestrian safety and comfort, static traffic order, diversity of commercial formats, quality of consumption environment, richness of social venues, pleasantness of spatial scale, landscape interactivity, and street navigability. These findings indicate that youth groups with varying interactive relationships with historic districts possess significantly heterogeneous needs regarding public space utilization, and their expectations for historic district regeneration also manifest differentiated characteristics. This provides a scientific basis for formulating precise, multi-layered strategies for district renewal.